Serum Vitamin D Status in Children with Pancreatitis - Parveen, Rezina; Ferdousi, Jannatul; Rukunuzzaman, Md; Karim, A S M Bazlul; Bayes, Farhana; Mahbub, Imteaz; Jubaere, AKM; Alam, MD Shafiul (Medicine Today, 2026)
Introduction and Objective: The incidence of pancreatitis in children has significantly increased in the past two decades. Fat-soluble vitamin deficiencies (A, D, E, K) can be seen in pancreatitis. This study evaluate serum vitamin D status in children with Pancreatitis. Methods: This cross sectional analytical study was conducted at the Department of Pediatric Gastroenterology and Nutrition, BMU, Dhaka, from January, 2022 to December, 2022. A total of 30 children with the diagnosis of Pancreatitis was included as cases (Group I) and 20 children with the diagnosis of functional constipation was included as control (Group II) in the study. Serum 25-hydroxyvitamin D levels <15, 15 to 19 and 20 ng/ml were defined as vitamin D ‘‘deficiency’’, ‘‘insufficiency’’ and “sufficiency” respectively. Results: Mean age of case was 8.48±4.16 years and control was 9.88± 2.68 years. Acute pancreatitis (AP) was 30%, acute recurrent pancreatitis (ARP) was 26.7% and chronic pancreatitis (CP) was 43.3% among the 30 patients. In AP, serum vitamin D level was 10.32-24.5 ng/ml and mean value was 15.06±4.33 ng/ml. In ARP, serum vitamin D was 9.4-26.1 ng/ml and mean value was 16.54±5.56 ng/ml. In Chronic Pancreatitis, serum vitamin D level was 4.24-15.4 ng/ml and mean value was 8.21±3.61 ng/ml. In controls, serum vitamin D level was 11.15-23.28 ng/ml and mean value was 16.15±3.55 ng/ml. Mean vitamin D level in pancreatitis patients were 12.49±5.73 ng/ml, compared to 16.15±3.55 ng/ml in controls (p = 0.014), it was found statistically significant. Vitamin D deficiency found in 66.7% patients in case (group I). Serum calcium was found to have statistically significant positive correlation with vitamin D level (r=0.633; p=0.001). Conclusion: Serum vitamin D level was low in patients with pancreatitis compared with control group. Medicine Today 2026, Vol.38 (1): 19-24